2019
DOI: 10.1049/iet-cds.2018.5187
|View full text |Cite
|
Sign up to set email alerts
|

All‐spin logic XOR gate implementation based on input interface

Abstract: An input interface for all-spin logic (ASL) circuits is proposed, which is composed of magnetic tunnel junction (MJT) and metal wires that are used for transmitting electrical signals. The proposed input interface can shorten the length of nonmagnetic channel and avoid the complex fan-out structure, and is fit for the circuits that need multiple same input signals. Moreover, based on the ASL minority gate and inverter, two kinds of XOR gates are designed. Compared with the XOR gate without input interface, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…If the channel length is more than spin diffusion length, then spin-flip would take place, hampering the functionality of ASL devices. There are various applications developed using ASL devices such as full adder [254,255], Boolean logic gates [255][256][257], and arithmetic logic unit [258]. A detailed review of ASL devices can be found in Refs.…”
Section: All Spin Logic Devicementioning
confidence: 99%
“…If the channel length is more than spin diffusion length, then spin-flip would take place, hampering the functionality of ASL devices. There are various applications developed using ASL devices such as full adder [254,255], Boolean logic gates [255][256][257], and arithmetic logic unit [258]. A detailed review of ASL devices can be found in Refs.…”
Section: All Spin Logic Devicementioning
confidence: 99%
“…In particular, ASL does not require additional hardware for repeated spin-charge conversion, which has attracted considerable attention [11][12][13][14][15][16][17][18]. Various types of logic circuits based on ASL have been proposed, such as full adder [19], D flip-flop [20], RS flip-flop [21], and XOR gate [22]. However, as an important element in logic circuits, the decoder has not been reported in the public as much as we know.…”
Section: Introductionmentioning
confidence: 99%
“…But, fortunately, ASLD does not need extra hardware for implementing spin-charge conversion repeatedly, because spin is used at every stage of information processing, transfer, and storage [8]. Thus, ASLD is relatively simpler than other spintronic devices in structure and has been widely studied in the aspects of device switching mechanism [9][10][11], material and structural optimization [12][13][14][15][16][17][18][19][20][21][22][23], and circuit design [24][25][26].…”
Section: Introductionmentioning
confidence: 99%